Modulating the complement system through epitope-specific inhibition by complement C3 inhibitors - Chen, Zhidong; Wang, Mingshuang; Duan, Wenqian; Xia, Yi; Liu, Huiqin; Qian, Feng (The Journal of biological chemistry, 2025)
As an integral part of the innate immune system, the complement system is a tightly regulated proteolytic cascade, playing a critical role in microbial defense, inflammation activation, and dying host cell clearance. Complement proteins are now emerging as subjects of intense research and drug development, since dysregulation of the complement system plays a critical role in several diseases and disorders, such as paroxysmal nocturnal hemoglobinuria (PNH) and geographic atrophy (GA). Within the complement cascade, complement C3 is the central component, situated at the convergence of all complement activation pathways, rendering it an attractive target for complement-related diseases. However, due to the complicated structure-activity relationship (SAR) of C3, elucidating the mechanisms of C3 inhibition on diverse epitopes is the basis for the rational design of C3-targeted therapeutics. Here, we have developed a set of comprehensive biochemical assays that are tailored to the specific steps within the complement cascade, allowing for a thorough understanding of the pharmacological consequences of different C3 inhibitors at each stage. Utilizing three model inhibitors (MIs) with different epitopes, we found that inhibition of MG4/MG5 domains has potent inhibition efficacy across all the complement activation pathways by interrupting C3-C3 convertase interaction, while inhibition of C345C domain displays a bias over the Alternative pathway (AP) inhibition by impairing AP C3 proconvertase formation. This study elucidates the intricate impact of C3 inhibition by targeting different epitopes, offering valuable insights into understanding the mechanism and facilitating the rational design of C3-targeted therapeutics. [Display omitted]